Emodin induces apoptosis of concanavalin A-stimulated murine splenocytes - An, Subin (Food Sci Biotechnol, 2016)
Emodin, one of the major compounds in the herb Reynoutria elliptica, is known to maintain immunosuppressive, anti-allergic, anti-cancer, and anti-inflammatory effects. In this study, we assessed the possibility of using emodin to induce apoptosis in stimulated immune cells in vitro. After treatment with emodin and concanavalin A (Con A), we observed DNA damage-induced apoptosis in splenocytes. Moreover, treatment with emodin and Con A increased the number of apoptotic splenocytes compared with untreated controls. Emodin also diminished the size of CD45R/B220(+) cells, CD19(+)CD69(+) cells, and cDC populations. These results indicate that emodin-induced apoptosis was involved in attenuating the immune activity promoted by DNA damage and in decreasing the number of CD45R/B220(+) B cells and CD19(+)CD69(+) activating B cells. This demonstration of emodin inducing apoptosis of Con A-stimulated immune cells indicates its potential utility as a therapy for diseases caused by abnormally activated immune cells.